Triisopropylsilyl (TIPS) Alkynes as Building Blocks for Syntheses of Platinum Triisopropylsilylpolyynyl and Diplatinum Polyynediyl Complexes - Weisbach, Nancy; Kuhn, Helene; Amini, Hashem; Ehnbom, Andreas; Hampel, Frank; Reibenspies, Joseph H.; Hall, Michael B.; Gladysz, John A. (Organometallics, 2019)
Hay oxidative cross coupling (O2/CuCl/TMEDA) of trans-(p-tol)(p-tol3P)2Pt(CC)2H (PtTC4H) and excess H(CC)2Si-i-Pr3 (TIPSC4H) gives PtTC8TIPS (55%). Subsequent addition of n-Bu4N+F- and repetition of the Hay protocol yields PtTC12TIPS (56%) and the byproduct trans-i-Pr3Si(CC)2(p-tol3P)2Pt(CC)6Si-i-Pr3 (TIPSC4PtC12TIPS, 5%); another cycle gives PtTC16TIPS (13%). Analogous cross couplings of trans-(C6F5)(p-tol3P)2Pt(CC)2H (PtFC4H) and excess TIPSCxH yield PtFC6TIPS (x = 2, 58%) and PtFC8TIPS (x = 4, 23%). Each is treated with n-Bu4N+F-, and repetition of the Hay protocol with TIPSC4H gives PtFC10TIPS (58%) and PtFC12TIPS (47%). When the Hay conditions are applied to PtFCxTIPS (x = 6, 8, 10, 12) without a cross-coupling partner, homocoupling to PtFC2xPtF occurs (68-99%). The reaction of trans-(p-tol3P)2PtCl2 and TIPSC4H (4.5 equiv; cat. CuI, CH2Cl2/HNEt2) yields TIPSC4PtC4TIPS (95%). Hay cross coupling of HC4PtC4H and excess TIPSC4H gives TIPSC4PtC4TIPS (6%), TIPSC4PtC8TIPS (12%), TIPSC8PtC8TIPS (10%), TIPSC4PtC12TIPS (7%), and TIPSC8PtC12TIPS (3%). Although TIPS can be a superior protecting group, it offers no advantage vs triethylsilyl in the preceding reactions. The crystal structures of PtTC8TIPS, PtTC12TIPS, PtFC6TIPS, PtFC8TIPS, TIPSC4PtC4TIPS, TIPSC8PtC8TIPS, TIPSC4PtC12TIPS. and PtFC20PtF are determined. The last is the longest dimetallapolyyne so characterized to date. The 13C NMR chemical shifts of the sp carbon atoms are accurately modeled by DFT calculations.
CRIS-Team Scopus Importer:2019-09-17